What Is Higher Education For: A Review with Recommendations [In Bulgarian] - B. V. Toshev (University of Sofia, 2015)
This article advocates for a substantial change of the structure of the higher education system in Bulgaria for its closer correspondence with the university traditions and the modern educational practices.